Enhancing Supply Chain Visibility in the Fishing Industry: The Role of Emerging Technologies and Their Affordances - Mirzaei, M; Dehe, B; Weerasinghe, K; Srivastava, H (OSCM Publications, 2025)
This study explores the role of emerging technologies in enhancing supply chain visibility (SCV) within New Zealand's fishing industry, a sector challenged by the perishable, temperature-sensitive nature of its products, subject to long supply routes, and strict regulatory standards. In this context, visibility within the supply chain transcends mere tracking; it encompasses real-time data access on product status, environmental conditions, and logistical status. Leveraging the technology affordance theory, the research examines how tools such as GPS trackers, RFID tags, and IoT devices influence decision-making and operational efficiency by offering actionable data insights. Through a qualitative case study, including interviews and workshops with industry experts, the article identifies key technological affordances: real-time tracking, proactive management, and data-driven decision-making. The theory of technology affordances provides insights into the interactions between technology and the socio-technical environment, highlighting the opportunities and challenges industry managers face. Our analysis reveals that while these technologies substantially improve monitoring and sustainability practices, their effectiveness is tempered by user knowledge, contextual conditions, and organizational collaboration. Moreover, the study highlights the complex interactions between technology, user expectations, and supply chain outcomes, emphasizing the need for integrated, user-centric platforms to maximize SCV benefits. This research contributes by providing a nuanced understanding of the factors linking SCV technologies, functionalities, and decisions through their adoption and impact. The mapping offers practical insights for supply chain managers to enhance transparency, resilience, and efficiency. Ultimately, the study encourages continued innovation in data- driven SCV solutions to address the unique challenges of perishable goods supply chains.